Relationship between Components of Quality of Work Life with Job Satisfaction among Midwives in mashhad, 2014 - Zahra Hadizadeh Talasaz; Shahla Nourani Saadoldin; Mohammad Taghi Shakeri (Tehran University of Medical Sciences, 2015)
Background & Aim: Quality of work life seems to have impact on employees' job satisfaction, job involvement, job performance, turnover, and organizational transformation. This study aimed to assess the relationship between job satisfaction with the components of quality of work life among midwives in mashhad .   Methods & Materials: This was a correlational study conducted among 230 midwives in mashhad in 2014. Data were collected using a demographic questionnaire, Walton's quality of work life, and the Minnesota job satisfaction questionnaire. Validity of the questionnaires was confirmed by 10 experts. The reliability was confirmed by alpha Cronbach. Data were analyzed using the descriptive statistics, Pearson, Spearman and ANOVA tests in the SPSS-19 .   Results: The overall quality of work life and job satisfaction had significant positive correlations (P<0.001; rp=0.525 ). The job satisfaction had correlation with fair and adequate payment (rp=0.277; P <0.001), safe working conditions (rp=0.274; P <0.001), proper opportunity promotion ( rp=0.306; P <0.001), o verall space of life ( rp=0.327; P <0.001), job lawfulness ( rp=0.233; P <0.001), social dependence in the work life ( rp=0.207; P <0.001), s ocial cohesion in the organization (rp=0.352; P <0.001), and proper opportunities to develop human capabilities (rp=0.259; P <0.001) .   Conclusion: Higher quality of work life is correlated with the higher job satisfaction. Managers can plan and implement appropriate strategies to promote components of quality of work life of midwives to provide efficient health services .